Mountains and borders, geographical approaches from the South. An Araucanía-North Patagonia case study - Matossian, Brenda (2016)
Argentina and Chile share the third world?s longest international land boundary (5,150 km) delineated by the mountains of the southern section of The Andes. Complex relationships, migratory and commercial exchanges, as well as imaginaries/representations and policies concerning nature conservation and cultural heritage preservation have either divided or brought both countries together, throughout their history as Nation States and neighbors.Argentine and Chilean academics have studied regional borderlands as rather watertight compartments. This tendency to reproduce in the scientific research field the social construction of borders as a limit or division has been modified over the last two decades. Critical and binational studies, from multiple disciplinary perspectives and scales, have explored the transformation of this space shared throughout history. This article collects and systematizes background studies on the Araucanía (Chile) and North Patagonia (Argentina) frontier to identify the main theoretical contributions from Geography and other Social Sciences which have improved debates on space in this borderland. This descriptive research is based on a theoretical and thematic analysis of both recent academic production and activities. Some of the conclusions are: (1) Currently, studies focus on the subjective dimensions of borders. (2) The notion of region as a living space enables us to give center stage to the treatmentof border subnational areas. (3) The notion of scale permits us toconnect power relations to the dialectics nationalism/internationalization, at interregional and intraregional level. (4) The concept of landscape unveils the importance of imaginaries/representations in the processes of territorialization and frontierization.